(untitled) (Konferensiyalar | Conferences, 2024)
In the field of ESL (English as a Second Language) education, the incorporation of interactive teaching methods plays a vital role in increasing student engagement, facilitating effective language acquisition, and nurturing a dynamic learning environment. Drawing on current educational research and pedagogical practices described in scholarly literature, this thesis emphasizes the transformative impact of interactive methodologies in ESL classrooms, emphasizing their relevance in meeting learners’ diverse needs and optimizing language learning outcomes.